The Research on Children and Early Childhood in the UNESCO Project (Translation) - Cruz, Ana Cristina Juvenal da; Abramowicz, Anete; Rodrigues, Tatiane Cosentino (Revista Eletrônica de Educação, 2015)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->DOI: http://dx.doi.org/10.14244/198271991357 The paper presents a partial summary of the details of an ongoing survey aimed to analyze the research on children and childhood at the UNESCO research program implemented in Brazil, known as “UNESCO Race relations Project” (MAIO, 2004), in partnership with Revista Anhembi, from São Paulo, Brazil, between 1950 and 1953. We integrate a genealogical methodology in order to recover the ideas that anticipated thinking about race relations and children from Virgínia Leone Bicudo’s (1955) “Atitudes dos alunos dos grupos escolares em relação com a côr dos seus colegas” (“Attitudes of schoolchildren regarding the color of their schoolmates”) and Aniela Meyer Ginsberg’s (1955) “Pesquisas sôbre as atitudes de um grupo de escolares de São Paulo em relação com as crianças de côr” (“Research on the attitudes of a group of schoolchildren of São Paulo towards colored children”). The studies indicate a protagonism of racial thinking about children’s ways of socialization, a central theme to contemporary studies, the agency of the child and, in a specific way, the specificity of the agency in terms of race relations. These studies have a precursor character, as they investigate categories as race, gender, nationality, age and social class in an articulate way. Our emphasis is to constitute the historical context in which the Brazilian social sciences developed as a field of study and research in which the issues regarding children and their childhoods are marked by the variability of gender, race, and social class experiences. We seek to conciliate a diachronic sequence in which the authors’ investigations are inserted within the themes of contemporary research on childhood and race relations. Keywords: Race relations, Childhood, UNESCO project.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->